A Prescription for Internet: Feasibility of a Tablet Loaner Program to Address Digital Health Inequities - Brewster, Ryan C.L.; Zhang, Jessica; Stewart, Melissa; Kaur, Ravneet; Arellano, Marlíse; Bourgeois, Fabienne (Applied Clinical Informatics, 2023)
Objective The coronavirus disease 2019 pandemic accelerated the adoption of telehealth technologies. Persistent disparities in telecommunication devices, internet connectivity, and digital literacy, however, undermine the potential for telemedicine to reduce barriers to health care access. Health systems may have a role in addressing these structural inequities. We describe the operationalization and feasibility of an internet-enabled tablet loaner program at a freestanding children's hospital.Methods Between October 2020 and October 2021, pediatricians enrolled families through ambulatory clinics at an academic urban freestanding children's hospital. Eligibility criteria included difficulty accessing virtual care due to lack of stable internet or device. Tablets featured an unlimited data package, access to the patient portal, and virtual visit platform. A private technology company managed device configuration and distribution. To characterize program impact, we compared the proportion of completed clinical encounters during the intervention compared with a preintervention period (March 2020–October 2020) and conducted a qualitative survey with program participants. Participant and visit characteristics were obtained from the electronic medical record and summarized with descriptive statistics.Results A total of 111 families participated in the tablet loaner program, the majority of whom were Hispanic (51.4%) and black, non-Hispanic (26.1%), and publicly insured (64.9%). Between the preintervention and intervention periods, there was a significant increase in completed video- and phone-based virtual visits (75.3 vs. 79.1%, p = 0.038). The proportion of video-based only visits increased from 82.9 to 88.9%. p < 0.001. Families reported that the tablet improved the patient's ability to receive medical care (93.7%) and was easy to use (93.9%).Conclusion The tablet loaner initiative was associated with an improvement in markers of virtual visit engagement and health care experience. Efforts to expand telemedicine equity must consider technological access and digital literacy as well as broad coalitions across industry, government, and community organizations.
Keywords: at-risk populations; telemedicine; telehealth; socioeconomic disparities; outcomes; implementation model; children; internet; technology